A domonkos szentek tiszteletének népszerűsítése a szombathelyi rendházban a XVII-XVIII. században - Zsámbéky Mónika (2001)
The author analyses the 17th-18th century pieces of furniture in the St. Martin Church. She claims that the Order of St. Dominic at the formation of the altars emphasized the cult of Virgin Mary and the saints of the order by putting their pictures and sculptures on the altars. By this they strengthened the veneration of the order's saints and their own community. The author found similar aspirations in other Dominican churces, as well (in Sopron, Vasvár, Graz, Vienna, Krems and Pettau).
Keywords: Bölcsészettudományok; Történettudomány és régészet; Filozófia, etika és vallástudományok